EFEKTIVITAS KELANCARAN LALU LINTAS PADA RUAS TOL CAWANG-TOMANG–CENGKARENG - Paul Sipoh; Adenan Suhalis; Miskul Firdaus (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
PT Jasa Marga (Persero) Tbk. being a modern company in the development and operation of Toll Road, being a leader (Leader) in the Toll Road industry by operating the majority of Toll Roads in Indonesia and has a high competitiveness at National and Regional level. The purpose of this study is to determine the implementation of traffic signs and effectiveness smoothness of toll road traffic that occurred in Cawang-Tomang-Cengkareng toll road (CTC) at PT Jasa Marga (Persero) Tbk. Year 2016 as well as integration between the implementation of traffic signs with the effectiveness of traffic smoothness. Based on research conducted on traffic sign implementation variable in Cawang-Tomang-Cengkareng toll road PTJasa Marga (Persero) Tbk. In 2016 considered good this is evidenced by the percentage of 52.3% of respondents gave Agreed answers. Variable of effectiveness of traffic smoothness in Cawang-Tomang-Cengkareng toll road of PT Jasa Marga (Persero) Tbk Year 2016 is considered good as evidenced by the large percentage of respondents who gave Agreed answer of 62.7%. based on the calculation of the correlation done in the results can be that the integration between the implementation of traffic signs and the effectiveness of the smoothness of traffic is declared strong because the results obtained 0.695 this shows a strong integration. The sample used is the driver of the vehicle on the Cawang-Tomang-Cengkareng toll road. With 30 respondents.